2016
DOI: 10.1108/ijlss-06-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Lean manufacturing practices in Indonesian manufacturing firms

Abstract: Purpose Contradictory findings regarding the implication of Lean manufacturing (LM) implementation to business performance (BP) have been observed in prior studies. Hence, more studies are required to be capable of finding the status of LM implementation and its impacts on BP. Accordingly, this study examines and scrutinizes the effects of LM practices on the enhancement of BP from a developing country standpoint. Design/methodology/approach This empirical study uses a survey-based quantitative data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 71 publications
6
71
0
1
Order By: Relevance
“…Thus, the different inventory management practices have significant relationships with operational performance of the manufacturing firms in Ghana. This finding is in line with previous studies by [69,98,120,121] who found positive relationships between inventory management practices (IMP) and performance of manufacturing firms in developing economies including Kenya, Nigeria and Ethiopia. The established regression model for the study using the standardized coefficients was:…”
Section: Inventory Management Practices and Operational Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the different inventory management practices have significant relationships with operational performance of the manufacturing firms in Ghana. This finding is in line with previous studies by [69,98,120,121] who found positive relationships between inventory management practices (IMP) and performance of manufacturing firms in developing economies including Kenya, Nigeria and Ethiopia. The established regression model for the study using the standardized coefficients was:…”
Section: Inventory Management Practices and Operational Performancesupporting
confidence: 93%
“…It works efficiently when there are clear agreements with suppliers for short cycle deliveries [66]. It has largely been found to improve operational performance in areas of operational flexibility, dependability, speed while minimising inventoryrelated costs [65,67,68,69]. Other studies similarly found JIT to positively influence operational performance in terms of timely deliveries, waste elimination, increased productivity while improving demand management [70,71,72].…”
Section: Just In Time and Operational Performancementioning
confidence: 99%
“…More recently, Fullerton and Wempe (2009) and demonstrated that the mixed results of prior studies regarding the LM and business performance relationship may be due in part to a failure to account for non-financial manufacturing performance measurement. Although variations exist in performance effects of LM, industrial reports have provided enough evidence that LM can potentially increase financial performance through improving organizational processes and cost efficiencies, both in developed and developing countries, and even among smaller firms (Fullerton et al, 2003;Fullerton and Wempe, 2009;Ghobakhloo and Azar, 2018b;Godinho Filho et al, 2016;Nawanir et al, 2016). LM practices can also enhance manufacturing productivity by reducing setup time and work in process inventory, improving throughput times (Tu et al, 2006;Yang et al, 2011).…”
Section: The Role Of Lean Manufacturing Effectivenessmentioning
confidence: 99%
“…performance measures were selected to evaluate SC performance based on the fact that these measures are the most common measures used in the majority of researches and recent in dates e.g. (Chavez et al, 2013;Taj & Morosan, 2011;Nawanir et al, 2016;Arif-Uz-Zaman & Ahsan, 2014;Ruiz-Benítez et al, 2018;Filho et al, 2016;Sharma et al, 2015;Shah & Ganji, 2017;Prajogo et al, 2016;Khanchanapong et al, 2014;Azfar et al, 2014;Dora et al, 2016;Kumar et al, 2015;Afonso & Cabrita, 2015;Droge et al, 2004, Jacobs et al, 2007Machuca et al, 2011;Rosenzweig et al, 2003;Folinas et al, 2014 ;Sangwa & Sangwan, 2018;Arif-Uz-Zaman & Ahsan, 2014;Behrouzi &Wong, 2011;Chavez et al, 2015). From which, the measures were classified into four different performance attributes (cost, time, quality, flexibility), those attributes are highly common in these researches that have discussed lean practice and performance topics.…”
mentioning
confidence: 99%
“…Therefore, this study included all SC performance measures to encompass the whole SCOR model processes that constitute SC processes based on the performance attributes that are commonly used to assess lean practice on performance. This can be indicated as the following table 3-3: Return on investment ratio (Chavez et al, 2015;Afonso & Cabritab, 2015;Nawanir et al, 2016) Value added productivity (Ruiz-Benítez et al, 2018;Chavez et al, 2015) Production efficiency…”
mentioning
confidence: 99%